Rapid Naloxone Administration Workshop for Health Care Providers at an Academic Medical Center - Raagini Jawa; Thuy Luu; Melissa Bachman; Lindsay Demers (Association of American Medical Colleges, 2020)
Introduction Opioid overdose is a growing problem in the US. Often, residents are first responders to community and in-hospital opioid overdoses, and so, hands-on naloxone administration education is necessary. While residents get a brief algorithm on suspected opioid overdose during their mandatory American Heart Association basic life support training, there is a lack of hands-on standardized curricula on how to administer this lifesaving medication. Methods To fill this gap, we developed a hands-on workshop for medical trainees on how to respond to an opioid overdose. Trainees who completed our workshop left with a first-responder naloxone kit using the Massachusetts statewide open prescription. All attendees were asked to take a voluntary pre- and posttraining survey. Results A total of 80 trainees from a variety of specialties and training levels participated in this workshop. We were able to successfully link the pre- and postdata of 29 participants. Trainees were assessed on comfort in administering naloxone as a first responder and in teaching patients how to administer naloxone (via a 5-point Likert scale) and on percentage of time they prescribed naloxone to high-risk patient populations. We saw statistically significant increases in comfort in using naloxone and comfort in teaching patients to administer naloxone. Discussion This innovative curriculum provides an adaptable, short, and effective workshop with hands-on practice for medical trainees at a variety of training levels. The workshop can efficiently train future health care professionals how to approach an opioid overdose.